'How May I Serve You?': Report on online working. Issue 1 (1st December 2020) - Oliva, José García
Hidden workers behind offshore outsourced online customer services are still suffering significant consequences inherited from colonial systems. The report is based on a review of 158 live-chat conversations between the online audience and two customer service agents based in Pakistan and outsourced by UK companies. This online chat platform was created and designed for the participatory art project 'How May I Serve You'. Analysis of the conversations demonstrated how outsourced companies survey employees chats and physical behaviours, threaten pay cut or dismissal, and demand that the agents lie about their identity. Further research is needed to identify practical solutions to enhance employees' working conditions when working in the online customer service industry.